INVESTIGATION OF KONDAGOGU GUM TO DEVELOP TRANSDERMAL FILM OF REPAGLINIDE - Srikanth Reddy, Poreddy; Subhash Chandra Bose, Penjuri; Sruthi, Vuppula; Saritha, Damineni (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: In the present study, an attempt was made to develop polymeric blend transdermal patch of repaglinide using hydroxypropyl methyl cellulose (HPMC) K4M and kondagogu gum. Methods: A series of repaglinide drug-incorporated HPMC K4M-kondagogu gum matrix films were prepared by solvent casting method. The prepared transdermal films were evaluated for various parameters such as thickness, tensile strength, folding endurance, % elongation, % moisture content, % moisture uptake, % drug content, in vitro drug release, and drug excipient compatibility. Results: The Fourier-transform infrared spectra of the pure drug as well as drug-incorporated formulation indicated that no chemical interaction occurred between the drug and the polymers used. Differential scanning calorimetry thermograms of the pure drug and prepared formulation indicated that the drug has dispersed in micron level in the prepared films. In vitro release study data of prepared formulations were fitted into various mathematical models, and the best-fit model was found to be Higuchi model. Conclusion: Among all the formulations studied, the formulation F4 was found to be an optimized composition for efficient transdermal delivery of repaglinide for 24 h study period. Stability studies of the drug formulations concluded that the drug was stable in the optimized formulation for the study period.